2005
DOI: 10.1080/01443610500328231
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of family planning among Igbo women of south-eastern Nigeria

Abstract: A total of 200 Nigerian women visiting Nnamdi Azikiwe University Teaching Hospital's antenatal clinic were interviewed about their knowledge, attitude and practice of family planning. About 90% were literate. Their knowledge (80%) and approval (87%) of family planning was high, but the practice of modern family planning was low (25%) with most women involved in Billings/safe period (56%). The common methods used were Billings/safe period, condom, withdrawal and the intrauterine contraceptive device (IUCD). A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 4 publications
4
22
2
1
Order By: Relevance
“…Male involvement in family planning increases uptake of contraceptives [34]. Conversely, men are usually left out when decisions about reproductive health issues are discussed [19]. This may have a negative impact on women's decision to use contraceptives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Male involvement in family planning increases uptake of contraceptives [34]. Conversely, men are usually left out when decisions about reproductive health issues are discussed [19]. This may have a negative impact on women's decision to use contraceptives.…”
Section: Discussionmentioning
confidence: 99%
“…This may have a negative impact on women's decision to use contraceptives. Sometimes women fail to use contraceptives because of rejection by their spouses [19]. It is important that women in Malawi are empowered to make their own decisions on use of contraceptives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, most of the FP providers in Yemen are usually females, especially nurses and midwives, who have high accessibility, acceptability and good trust by women (24). It has been observed in Tanzania and Zambia that healthcare workers and government health facilities, such as hospitals, were the main source of information, while mass media was the main source of information about modern contraceptives in India and Nigeria (18,(23)(24)(25). Meanwhile, it was found that Indian women seeking voluntary termination of pregnancy had gained knowledge of contraceptives mostly from friends and family members (3).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the main source of information about FP was from healthcare providers followed by mass media, family members and friends. This may reflect the success of education, duties, publicity and regular action in FP by healthcare workers (23). Furthermore, most of the FP providers in Yemen are usually females, especially nurses and midwives, who have high accessibility, acceptability and good trust by women (24).…”
Section: Discussionmentioning
confidence: 99%